New insights into the stability of a high performance nanostructured catalyst for sustainable water electrolysis. (October 2017) - Siracusano, Stefania; Hodnik, Nejc; Jovanovic, Primoz; Ruiz-Zepeda, Francisco; Šala, Martin; Baglio, Vincenzo; Aricò, Antonino Salvatore
Abstract: Water electrolysis is a very promising technology for sustainable hydrogen generation using renewable electrical energy. The excellent performance and dynamic behavior for storing electrical energy in hydrogen allow polymer electrolyte membrane (PEM) electrolysis to cover the gap between the intermittent renewable power production and the grid demand at different time horizons and scales. This work is addressed to the development and characterization of high performance nanostructured Ir-Ru-oxide electro-catalyst achieving for the rate determining oxygen evolution reaction a current density of 3 A cm −2 at about 1.8 V (> 80% enthalpy efficiency) with a low catalyst loading (0.34 mg cm −2 ). The stability characteristics were studied in practical PEM electrolysis cells operating at 80 °C, using several durability tests of 1000 h each to evaluate the reliability of this electro-catalyst for real-life operation. Further insights on the degradation mechanism were acquired by subjecting the catalyst to potential steps in a specially designed electrochemical flow cell under corrosive liquid electrolyte with on-line monitoring of the dissolved ions. Structural, morphology, composition and surface analysis of the anode electro-catalyst after operation in the electrolysis cell, complemented by in-situ electrochemical diagnostics, provided important insights into the degradation mechanisms. Catalyst operation at high turnover frequency (TOF) was observed to cause a progressive change of Lewis acidity characteristics with time for both Ir and Ru cations thus influencing their ability to promote water oxidation. Graphical abstract: Highlights: Ir-Ru oxide catalysts (loading < 0.35 mg cm −2 ) achieve 3 A cm −2 with efficiency > 80%. Degradation during 1000 h tests increases mainly with operating turn over frequency. Modification of Lewis acidity for Ir and Ru sites is responsible for performance loss. Dissolution of Ir-Ru active species occurs according to their occurrence on the surface.